1989
DOI: 10.1097/00004032-198908000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Synopsis of French Experimental and in Situ Research on the Terrestrial and Marine Behavior of Tc

Abstract: Terrestrial environment studies have been essentially concerned with the evolution of soil deposition and soil-plant transfers. Experimentally determined coefficients of distribution in soils are low: 60-80% of Tc remains hydrosoluble during the first months. Technetium emissions resulting from microbiological activity have been quantified. Antagonistic effects on Mo and Tc retention by soils are dependent on their respective concentrations. Four areas of soil-plant transfers have been studied: 1) root absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Again, the assessment model was run both with and without default biokinetic parameters, with the macrophyte and winkle reference organisms chosen to illustrate the comparison. For these organisms, the default T B1/2 for 99 Tc in winkles is set to 142 days (Swift, 1989), whilst Tc in macrophyte is modelled with a biphasic release with T B1/2 s of 1.5 and 128 days, respectively (Masson et al, 1989;Busby, 1998;Topcuoglu and Fowler, 1984).…”
Section: Discharges From Sellafield 1952e2005mentioning
confidence: 99%
“…Again, the assessment model was run both with and without default biokinetic parameters, with the macrophyte and winkle reference organisms chosen to illustrate the comparison. For these organisms, the default T B1/2 for 99 Tc in winkles is set to 142 days (Swift, 1989), whilst Tc in macrophyte is modelled with a biphasic release with T B1/2 s of 1.5 and 128 days, respectively (Masson et al, 1989;Busby, 1998;Topcuoglu and Fowler, 1984).…”
Section: Discharges From Sellafield 1952e2005mentioning
confidence: 99%
“…Further, Masson et al (1989) reported that, during long-term percolation experiments on a calcareous soil, Mo applied to the soil surface (2 µg-200 µg kg Ϫ1 soil) increased the soil water migration of Tc, thus revealing a competitive effect between the two anions in the soil. Further work by Masson et al (1989) found that soil to plant transfer of 99 Tc in Lactuca sativa was inversely proportional to the soil molybdenum concentration applied. These data indicate that it might be useful to investigate further the role of MoO 2Ϫ 4 nutrition in 99 Tc uptake by plants.…”
Section: Tc Uptake and The Transport Of Other Ionsmentioning
confidence: 98%
“…Oxidation of 99 Tc compounds is probably so slow that accumulation of 99 Tc is possible in soils that are subjected to periodic waterlogging Muramatsu, 1993, 1995;Tagami and Uchida, 1999). However, there are a number of reports of 99 Tc being remobilised from marine sediments (Masson et al, 1989;Leonard et al, 1997;Morris et al, 2000). Low redox potentials can also cause TcO Ϫ 4 to react with hydrogen sulphide to form Tc 2 S 7 which is not available to plants (Brookins, 1988;Tagami and Uchida, 1996;Tagami and Uchida, 1997).…”
Section: Tc In Aerobic and Anaerobic Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In acid soils, both the water-soluble and the organic forms of technetium-99 are predominant, whereas water-extractable forms seem to predominate in calcareous soils (Masson et al 1989). The solubility and plant availability of technetium-99 are reduced over time, suggesting that it undergoes reduction (+4) and reoxidation (+7) in surface soils (Cataldo et al 1989).…”
Section: Technetium-99mentioning
confidence: 99%